PENGARUH JUMLAH UANG BEREDAR, KURS, DAN SUKU BUNGA PASAR UANG ANTAR BANK TERHADAP TINGKAT SUKU BUNGA BI 7-DAY (REVERSE) REPO RATE DI INDONESIA PERIODE 2017(M10) – 2019(M12) - Fitri, Yurindra; Rosyeti, Rosyeti; Rahmmat, Richard (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to analyze the effect of the money supply, exchange rate, and the interbank money market on the BI 7-Day repo rate in Indonesia for the 2017M10 - 2019M12 period. The method used in this research is descriptive and quantitative methods. The analysis model used is multiple linear regression analysis with the help of the Eviews 10 application, where the final result measures the influence of the money supply, exchange rates, and the interbank money market on the BI 7-Day repo rate in Indonesia for the 2017m10 - 2019m12 period. The results of this study indicate that the money supply and the interbank money market have a positive and significant effect on the BI 7-Day repo rate in Indonesia, while the exchange rate has a positive and insignificant effect on the BI 7-Day repo rate in Indonesia.Keywords :BI 7-Day repo rate, money supply, exchange rate, interbank money market